Project Based Learning dengan Pendekatan STEM pada Pendidikan Sekolah Dasar - Ni Made Yeni Suranti; Baiq Yuni Wahyuningsih (Indonesian Journal of Elementary and Childhood Education, 2024)
This literature review research aims to analyze findings from literature related to PjBL with a STEM approach in elementary schools. This research uses the descriptive content analysis study method. Analysis was carried out on international, national articles and similar sources related to PjBL with a STEM approach. This research was conducted to obtain a deeper understanding of the respective learning and implementation of PjBL with STEM at the basic education level. This learning is an effective solution to activate classroom learning. Project-based learning integrated with STEM in elementary schools has a positive impact on learning performance by encouraging hands-on learning, developing key skills such as collaboration and communication, and making learning interesting and relevant. This approach not only improves academic achievement but also prepares students to face future challenges and opportunities